The great North American stage directors Volume 1 - Belasco, David; Hopkins, Arthur; Webster, Margaret; Black, Cheryl, 1954- (London ; New York : Methuen Drama, 2021)
"Each volume provides substantial treatment of three major directors, with each director considered by two specialists, combining analysis of the director's practical craft with accounts of the historical, cultural and theoretical context of their practice. Links between the featured directors and other artists and directors from the period are traced to round out the picture of influences and artistic development."--
v. 1. David Belasco, Arthur Hopkins, Margaret Webster: Broadway Luminaries / edited by Cheryl Black -- v. 2. Harold Clurman, Orson Welles, Margo Jones: The Director in the Company / edited by Jonathan Chambers -- v. 3. Elia Kazan, Jerome Robbins, Lloyd Richards: Urban Spaces, Poetic Realisms / edited by Harvey Young -- v. 4. George Abbott, Vinnette Carroll, Harold Prince: Musical Theatre Innovators / edited by Henry Bial and Chase Bringardner -- v. 5. Richard Schechner, Lee Breuer, Anne Bogart: Company Experiments / edited by Joan Herrington -- v. 6. Meredith Monk, Richard Foreman, Robert Wilson: Landscapes of Consciousness / edited by Ann Shanahan -- v. 7. Elizabeth LeCompte, Ping Chong, Robert Lepage: Multi-Media Interrogations / edited by David Z. Saltz -- v. 8. Jesusa Rodriguez, Peter Sellars, Reza Abdoh: Theatre in the Public Sphere ; edited by James Peck.
Set 1: Volumes 1-4: Establishing Directorial Terrains, pre-1970 -- Set 2: Volumes 5-8: Directors and the Theatrical Avant-garde, post-1970
Includes bibliographical references and index.
Keywords: Theatrical producers and directors -- North America; Theater -- Production and direction -- North America